MiR-185-5p Protects Against Angiogenesis in Polycystic Ovary Syndrome by Targeting VEGFA - Jingzan Wei; Yanyan Zhao (Frontiers Media S.A., 2020)
Polycystic Ovary Syndrome (PCOS) is a heterogeneous endocrine disease with high incidences in women of reproductive age. Although miR-185-5p (miR-185) was decreased in PCOS patients, the exact function of miR-185 on PCOS development still requires further investigation. In this study, rat injected with dehydroepiandrosterone (DHEA) was established as a PCOS model. A lentivirus carrying miR-185 was employed to examine its effect on PCOS symptoms. Then we performed the luciferase reporter assay to validate the interactions between miR-185 and vascular endothelial growth factor A (VEGFA). Finally, human ovarian microvascular endothelial cells (HOMECs) were induced by VEGF to explore the role of miR-185 in the angiogenic process. The results showed that miR-185 overexpression improved insulin level alteration and ovarian histological lesion in PCOS rats. We also found that miR-185 reduced the excessive angiogenesis as indicated by alterations of VEGFA, ANGPT1/2, PDGFB/D, α-SMA and CD31 in the ovary of PCOS rats. Luciferase reporter assay identified that VEGFA directly interacted with miR-185, and its expression level was negatively regulated by miR-185. The in vitro results further demonstrated that miR-185-induced suppression of cell proliferation, migration and tube formation was attenuated by VEGF in HOMECs. In summary, this is the first study to show that miR-185 can target VEGFA to inhibit angiogenesis, thus improving the development of PCOS. These findings develop a molecular candidate for PCOS prevention and therapy.